Green Belt-od železné opony k zelenému pásu života - Bartoš, M.; Kušová, D.; Těšitel, J.; Zemek, F. (František) (2011)
The Iron courtain dividend Eastern and Western Europe for almou 40 years cutting off contacts between people on both sides. Nature seized the deserted border areas. Today a string of beutiful habitats with rare plants and animals connects Europe’s landscapes and forms a living monument of European history. To preserve the Green Belt as the backbone of an ecological network, running from the Barents Sea to the Black sea, as a living monument and as a global symbol for transboundary cooperation in nature conservation and sustainable development. According to the analysis of the protection system along the Green Belt, the results of the classification were vector digized in geographic information system as a segmented borderline with identified CORINE classes and protection status assigned to the segments.